2014
DOI: 10.1007/s00380-014-0470-2
|View full text |Cite
|
Sign up to set email alerts
|

Implications of pentraxin 3 levels in patients with acute aortic dissection

Abstract: Acute aortic dissection (AAD) causes transient inflammation with occasional pleural fluid (PF) accumulation. Although pentraxin 3 (PTX3) is a vascular inflammation-related biomarker, little is known about PTX3 levels in patients with AAD. We explored the serial changes in plasma PTX3 levels and the association of peak levels with the amount of PF accumulation. Consecutive patients (n = 41) with Stanford type B AAD were enrolled, and blood samples for the measurements of serum albumin, plasma PTX3 and high-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Arao et al . [11] have recently explored the association of plasma PTX3 levels with the amount of pleural fluid accumulation in Stanford Type B AD patients. Their results demonstrated that the peak PTX3 level in patients with AAD was associated with the amount of transient pleural fluid accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arao et al . [11] have recently explored the association of plasma PTX3 levels with the amount of pleural fluid accumulation in Stanford Type B AD patients. Their results demonstrated that the peak PTX3 level in patients with AAD was associated with the amount of transient pleural fluid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…[11] This is because these inflammatory markers are produced differently. CRP is a short pentraxin produced in the liver in response to IL-6, whereas PTX3 is a long pentraxin produced by inflammatory and immune cells in response to IL-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTX-3 is expressed in advanced atherosclerotic lesions and is associated with cardiovascular risk factors [1], acute aortic dissection [2] and atrial fibrillation [3]. CRP is mainly produced by hepatocytes under inflammatory stimulation, whereas PTX-3 is directly produced by macrophages, endothelial cells, and smooth muscle cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, plasma Pentraxin 3 levels were associated with the amount of transient pleural fluid accumulation. Although at this time, the role of this biomarker in AD is not fully understood, it has been shown to be elevated in patients with acute lung injury, acute respiratory distress syndrome, and septic shock [25].…”
mentioning
confidence: 99%